2016
DOI: 10.1016/j.envpol.2016.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric concentrations and loadings of organochlorine pesticides and polychlorinated biphenyls in the Canadian Great Lakes Basin (GLB): Spatial and temporal analysis (1992–2012)

Abstract: Long-term air monitoring data for POPs are required to determine the effectiveness of source reduction measures and factors controlling air concentrations. Air samples were collected between 1992 and 2012 at three sites with different geographical characteristics (Burnt Island, Egbert and Point Petre) in the Canadian Great Lakes Basin (GLB) using high-volume samplers and analyzed for organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs). Spatial and temporal trends of gas-phase concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 46 publications
8
37
1
Order By: Relevance
“…The observed changes over time as reported in these articles are compound specific and demonstrate that the regulatory actions established since the 1980s in some regions and integrated in the global SC framework in 2004 have helped decrease the global concentrations of most older POPs (e.g. Cincinelli et al, 2016;Graf et al, 2016;Hung et al, 2016;Rig et et al, 2016;McGoldrick and Murphy, 2016;Venier et al, 2016;Shunthirasingham et al, 2016;Takazawa et al, 2016), but for some of the newer POPs and chemicals of emerging concern [e.g. per-and polyfluoroalkyl substances (PFASs)], clear temporal trends are still not observed Hung et al, 2016;McGoldrick and Murphy, 2016).…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…The observed changes over time as reported in these articles are compound specific and demonstrate that the regulatory actions established since the 1980s in some regions and integrated in the global SC framework in 2004 have helped decrease the global concentrations of most older POPs (e.g. Cincinelli et al, 2016;Graf et al, 2016;Hung et al, 2016;Rig et et al, 2016;McGoldrick and Murphy, 2016;Venier et al, 2016;Shunthirasingham et al, 2016;Takazawa et al, 2016), but for some of the newer POPs and chemicals of emerging concern [e.g. per-and polyfluoroalkyl substances (PFASs)], clear temporal trends are still not observed Hung et al, 2016;McGoldrick and Murphy, 2016).…”
mentioning
confidence: 83%
“…Camenzuli et al (2016) showed that pesticide concentrations are globally significantly higher in agricultural soil than background soil. Shunthirasingham et al (2016) also reported the highest air concentrations of organochlorine pesticides at an agricultural site compared to two other remote sites in the Great Lakes. These findings reflect the predominantly anthropogenic origin of POPs and their continued emissions from stockpiles, waste-streams and reemission from environmental sinks (e.g.…”
mentioning
confidence: 90%
See 3 more Smart Citations